2018
DOI: 10.1002/app.46740
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel supermacroporous molecularly imprinted cryogel membrane with a specific ionic liquid for protein recognition and permselectivity

Abstract: A novel supermacroporous molecularly imprinted cryogel membrane (MICM) was prepared via cryopolymerization using a functionalized ionic liquid {(1‐vinyl‐3–(2‐amino‐2‐oxoethyl) imidazolium chloride, [VAMIM]Cl]} as functional monomer. Bovine serum albumin (BSA) was selected as the model protein. The novel membrane has the advantages of several concepts, such as, the easy mass transport of cryogel, the multiple weak interactions of ionic liquid with protein, high selectivity of molecularly imprinted polymer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The result confirmed that with a well-controlled pore size distribution, the graphene NATMs can outperform the commercialized polymeric membranes in both permeance and selectivity. Moreover, the selectivity of graphene NATMs was notably higher than the selectivity achieved by isoporous membranes, molecularly imprinted cryogel membranes, silica colloidal crystal membranes, and track-etched membranes . Also, this value was comparable to the selectivity achieved in diffusion tests by gold nanotubule membranes .…”
Section: Resultsmentioning
confidence: 99%
“…The result confirmed that with a well-controlled pore size distribution, the graphene NATMs can outperform the commercialized polymeric membranes in both permeance and selectivity. Moreover, the selectivity of graphene NATMs was notably higher than the selectivity achieved by isoporous membranes, molecularly imprinted cryogel membranes, silica colloidal crystal membranes, and track-etched membranes . Also, this value was comparable to the selectivity achieved in diffusion tests by gold nanotubule membranes .…”
Section: Resultsmentioning
confidence: 99%
“…Membranes exhibited higher binding affinity with respect to those prepared without the ionic liquid. In addition, the selectivity factor for salicylic acid with respect to the competing compounds p-hydroxybenzoic acid and phenol was 5.85 and 5.90, respectively [ 278 ]. Fan and coauthors developed a macroporous cryogel-imprinted membrane using (1-vinyl-3-(2-amino-2-oxoethyl) imidazolium chloride as a functional monomer and bovine serum albumin as a model template protein [ 279 ], in a phosphate buffer as solvent and porogen.…”
Section: Green Molecularly Imprinted Membranesmentioning
confidence: 99%
“…Permeation tests carried out in a diffusion cell with solutions containing the template and the similar human serum albumin (having each one the concentration of 0.4 mg∙L −1 ) evidenced a high transport rate of the template molecules: the permeation amount of bovine serum albumin was 2.82 mg∙cm −2 , while that of the competing protein was 1.63 mg∙cm −2 [ 278 ].…”
Section: Green Molecularly Imprinted Membranesmentioning
confidence: 99%
“…Thus, MIMs were used for the depletion of albumin from neat solutions and biological samples [63][64][65][66]. An interesting example is that developed by Fan et al [65], where a supermacroporous MIM was prepared via cryopolymerization using a functionalized ionic liquid {(1-vinyl-3-(2-amino-2-oxoethyl) imidazolium chloride, [VAMIM]Cl]} as functional monomer and bovine serum albumin (BSA) as the template. The preparation scheme of this imprinted membrane and the schematic representation of the molecular imprinting procedures were depicted in Figure 16.…”
Section: Pharmaceutical and Food Applicationsmentioning
confidence: 99%